International Conference on Religious Environmentalism in Actions: Knowledge, Movements, and Policies. - Firda Amalia Putri; Saiful Umam (Studia Islamika, 2025)
The Center for the study of Islam and Society (PPIM), Syarif Hidayatullah State Islamic University (UIN) Jakarta under the project of Religious Environmentalism Actions (REACT) in collaboration with Faculty of Social Sciences, Indonesian International Islamic University Depok, and Studia Islamika, an international journal for Islamic studies in Southeast Asia (SEA) conducted the International Conference on Religious Environmentalism in Actions: Knowledge, Movements and Policies. This conference relies on the foundation that religious and spiritual communities are essential to the fight against environmental damage and climate change. And, it will also examine how policymakers promote collaborative interfaith engagement or develop collaborative partnerships with faith leaders and religious communities to generate more effective and long-lasting solutions for environmental and climate related problems.